THE EFFECTIVENESS OF THE 5E’S MODEL WITH ANALOGY IN PROMOTING STUDENTS’ DEEP UNDERSTANDING AND ATTITUDES TO LEARN SCIENCE IN BIOLOGY LEARNING - Purnomo, Purnomo; Kirana, Tjandra; Ibrahim, Muslimin (JPPS (Jurnal Penelitian Pendidikan Sains), 2013)
In evaluating the effectiveness of the 5Es model with analogy to providing access of deep understanding and attitudes to learn science, a case study research was brought involving 27 undergraduates who took The Human Anatomy and Physiology course. The data gathered were then analyzed using qualitative descriptive technique. The results informed that most students were successful to have deep understanding towards abstract concepts showing by grade of at least C or acceptable level and good attitudes  to  learn  science  within  which  all  students  possessed  the  same  perception  corresponding  to  interest  and  enjoyment regardless any different level of achievement. Overall, it could be concluded that the 5Es model with analogy was quietly effective to make deep understanding and attitudes to learn science appear in students? learning.Dalam mengevaluasi keefektifan model 5Es dengan analogi terhadap pemahaman mendalam dan sikap belajar sains, sebuah studi kasus dilakukan dengan melibatkan 27 mahasiswa yang memprogram Mata Kuliah Anatomi dan Fisiologi Manusia. Data yang diperoleh kemudian dianalisis dengan metode deskriptif kualitatif. Hasil penelitian tersebut menginformasikan bahwa umumnya siswa berhasil untuk memahami konsep yang abstrak secara mendalam yang ditunjukkan dengan nilai minimal C dan memiliki sikap belajar sains yang baik terkait dengan kesenangan dan minat belajar tanpa menghiraukan pencapaian hasil belajar mereka. Oleh karena itu, dapat simpulkan bahwa model pengajaran 5E dan analogi terbukti efektif untuk memunculkan pemahaman konsep secara mendalam dan sikap belajar sains.